AVALIAÇÃO DE ESPAÇAMENTOS DAS COLETAS DE SOLO PARA A MODELAGEM DE GRANULOMETRIA COM APLICAÇÃO NA AGRICULTURA DE PRECISÃO - Orlovski, Regiane (2013)
The Precision Agriculture relies on ground related factors especially granulometry and a potential way to get soil ground information is drawing developing soil maps.These maps can provide soil parameter variations such as granulometry and specifically clay contents. To get reliable soil maps a huge amount of field samples are necessary and it results in high costs mainly in gathering process and laboratory tests as well.The main goal of this study is to test different spacing techniques on getting ground sample belonging granulometry, clay contents, to the modeling process applied in precision agriculture, at Fazenda Escola Capão da Onça in Ponta Grossa city, Paraná state. Therefore, a normal grade and two transections were used due to topography using different spacing between soil sample gatherings. Also were tested different interpolators, comparing geostatic and non-geostatic. The study assumes that there is a necessity of technics to analysis soil parameter variations by distinguished studies of field samples. The methodology presented satisfactory outcomes according the way and the number of soil sample gathered evidencing that the clay granulometry variability is related to the way these samples are collected considering topography than the standard level of detail. Thus, the Southwest-Northeast transection collected with topography decrease was the one that have the best result compared to Northwest-Southeast transection with samples spacing between 80 and 100 meters.